A Historical Overview Of Poverty Eradication Through Agricultural In Sabah, Malaysia - Romzi Ationg; Rose Patsy Tibok; Madiyem Layapan; Andreas Totu; Wong, Jane Kon Ling; Lo, Alvie Sin Voi (2020)
This paper presents a comprehensive overview of the rural poverty eradication efforts undertaken by the Sabah state government by way of various agricultural- based solutions. The discussion examines local attitudes, behaviour and acceptance towards the contract farming system as a tool for agricultural commercialisation and the improvement efforts targeted at effecting changes in rural society structures and uplifting the rural standard of living. Sabah’s administrative history, its rural and agricultural sector economic development, and the social structures of rural society are deliberated upon extensively since these elements are found to be intricately interwoven in the incidence of rural poverty and the acceptance or willingness by rural communities to participate in poverty eradication programmes such as contract farming. Based on document reviews, participation in contract farming programmes is found to be static (neither increasing or declining) with the exception of rubber planting and paddy production which showed significant increase.